EDUKASI PEMASARAN DIGITAL DAN PELATIHAN BAHASA INGGRIS BAGI SISWA SD NEGERI 2 SERANGAN - intan Nirmalasari; I Made Trisna Semara; Putu Eka Wirawan; Ni Luh Putu Eka wahyuni; Ni Made Yulistia Dewi (Sewagati, 2024)
The Sanur Tourism Area, particularly Serangan Village, has significant tourism potential with its spiritual, marine, and culinary attractions. To support the development of Serangan Village it is essential to enhance the skills of the local community, especially in English language proficiency and the use of digital technology. At SD Negeri 2 Serangan, there are challenges related to the limited number of English language teachers and the students' low understanding of digital marketing. This activity aims to provide English language training and digital marketing education to students to enhance their competitiveness in the global era. The methods used include needs analysis, interviews, observations, as well as lectures and practical exercises in creating digital content. The results of this program show that digital marketing education helped students understand how to use social media to promote Serangan Village, while interactive English language training improved their language skills. Through this initiative, it is expected that the youth of Serangan Village will actively contribute to local tourism development and be better prepared for global challenges.